PENGARUH DISIPLIN KERJA TERHADAP PRESTASI KERJA GURU SMA NEGERI 4 BANDUNG (Jurnal Tata Kelola Pendidikan, 2021)
This research generally aims to reveal a clear picture of the effect of work discipline on teacher work performance. The research method used is a descriptive method supported by literature studies and by quantitative approaches. The population in this study was 30 respondents from teachers of SMA NEGERI 4 Bandung. Wms data processing results (Weight Means Score) that has been processed obtained the average result of variable score X of 4.27 which belongs to a very high category. As for variable Y obtained an average score of 4.04 which belongs to a very high category. Based on the results of the Normality Test, each variable is obtained that the calculated X2 value of variable X is 7,975 < the value of X2 table value is 11,070, it is declared normally distributed, while variable Y value X2 calculates 5,798 < the table X2 value is 12,592, it is declared normal distribution. Based on the results of the Correlation Coefficient Test obtained by the price of correlation coefficient (r) variable X to variable Y positive direction of 0.99, it can be concluded that the correlation coefficient between the two variables is at a very strong correlation coefficient level. Based on the results of the calculation of significant tests obtained the price of 1 count of 37.05 and the price of t table of 2,045, the correlation of variable X to variable Y is significant. While the coefficient of variable determination X terhdap variable Y by 98.01%. It can be concluded that the increase and decrease in teacher work performance is determined by the teacher's own work discipline of 98.01%, while the remaining 1.99% is determined by other factors. Based on the calculation result obtained price a and price b of 0.983, so the regression equation that describes the predicted score of variable direction Y based on variable X is Y = 0 + 0.983 X. The difference in the overall statistics test results can be concluded that " There is a Significant Influence between Work Discipline On The Prestassi Work of Teachers SMA NEGERI 4 Bandung ", proven to be true or acceptable.
Keywords: Teachers Work Performance; Work Discipline